Avaliação ambiental dos processos construtivos de estrutura metálica e pré-moldada de concreto por meio de análise do ciclo de vida - Mantovani, F.; Sebastiany, L. D.; Christ, R.; Mancio, M. (Revista ALCONPAT, 2013)
Concerns about the reduced availability of natural resources and the increased degradation of the environment have stimulated the appearance of new techniques which can help companies to implement a more environmentally sustainable production model. Because of that, new technologies and environmentally friendly materials have been developed, such as assessment systems and tools to support decision-making early on, during the design process. Life cycle analysis (LCA) emerges as a powerful tool for analyzing and choosing alternatives from an environmental perspective. This study provides experimental data on the flow of raw materials, products and waste, on the production process of a precast concrete column and a steel column. To make this analysis, the GaBi software was used. Results show that the steel column has greater environmental impact when compared with a reinforced concrete alternative. Keywords: Life cycle analysis; precast concrete structures; steel structures.